Association of the VEGF +405C/G gene polymorphism with diabetic retinopathy in an Indonesian (Yogyakarta) population - Supanji Supanji; Dewi Fathin Romdhoniyyah; Dinda Mutiara Maharani; Aurelia Priscilla Regita Putri; Hifdza Faza Felisha; Vera Nurohmah Indrawati; Ummi Noor Hasanah; Shanti Widya; Nurul Imawati; Eko Aribowo; Agit Seno Adisetiadi; Eva Revana; Tri Winarti; Muhammad Robikhul Ikhsan; Vina Yanti Susanti; Mohammad Eko Prayogo; Firman Setya Wardhana; Muhammad Bayu Sasongko (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2026)
Introduction: Diabetic retinopathy (DR) remains a major cause of vision loss, and while chronic hyperglycemia drives its pathogenesis, inconsistent findings on the VEGF +405G/C polymorphism and the absence of Indonesian data highlight the need to clarify potential genetic susceptibility. The purpose is to determine the association between the VEGF +405C/G rs2010963 gene polymorphism and the risk of diabetic retinopathy (DR) in an Indonesian population.Methods: Our observational case-control study enrolled 100 type-2 diabetes mellitus patients (50 DR patients vs. 50 non-DR) who underwent comprehensive clinical and ophthalmic examinations. Genomic DNA was extracted from peripheral blood samples, and the VEGF +405C/G rs2010963 polymorphism was genotyped using RFLP-PCR, with results confirmed by sequencing.Results: Our study included a total of 100 participants with no significant differences in baseline characteristics other than poorer visual acuity and significantly higher LDL and lower HDL levels in the DR case group. Allelic and genotypic distributions of the VEGF +405 rs2010963 polymorphism were similar between both groups, with HWE equilibrium analysis showing no significant deviation. Neither crude (GG; crude OR 0.32 [0.87 - 1.21]), age and sex-adjusted analysis (0.41 [0.11 - 1.60]), nor blood pressure, HbA1c level, BMI, and smoking status-adjusted OR of 0.38 (0.70 - 2.06), demonstrated a significant association between VEGF +405 rs2010963 polymorphisms and DR risk in our cohorts.Conclusion: Our study suggests that VEGF +405C/G polymorphisms may not serve as an independent risk factor for DR in the Indonesian population.